Efficient web browsing on handheld devices using page and form summarization. - Buyukkokten, Orkut (ACM transactions on information systems.)
We present a design and implementation for displaying and manipulating HTML pages on small handheld devices such as personal digital assistants (PDAs), or cellular phones. We introduce methods for summarizing parts of Web pages and HTML forms. Each Web page is broken into text units that can each be hidden, partially displayed, made fully visible, or summarized. A variety of methods are introduced that summarize the text units. In addition, HTML forms are also summarized by displaying just the text labels that prompt the use for input. We tested the relative performance of the summarization methods by asking human subjects to accomplish single-page information search tasks. We found that the combination of keywords and single-sentence summaries provides significant improvements in access times and number of required pen actions, as compared to other schemes. Our experiments also show that our algorithms can identify the appropriate labels for forms in 95% of the cases, allowing effective form support for small screens.